Cervical spondylotic myelopathy: the prediction of outcome following surgical intervention in 93 patients using T1- and T2-weighted MRI scans - Salem, Hatem M I; Salem, Khalid M I; Burget, Filip; Bommireddy, Raj; Klezl, Zdenek (European spine journal, 2015)
INTRODUCTION: Cervical spondylotic myelopathy (CSM) can lead to significant disability through a spectrum of clinical manifestations ranging from dexterity loss to more profound weakness, incontinence and paralysis. AIM: To determine the outcome of surgical decompression for CSM and investigate pre-operative predictors of outcome. METHODS: Prospectively collected data on all patients who underwent decompressive surgery for CSM and completed 12-month follow-up were reviewed. Data on age, MRI T1 and T2 signal changes pre-operatively, surgical approach and the Nurick's Myelopathy Grade (NMG) was analysed pre-operatively and 1 year post-surgery. RESULTS: Data on 93 consecutive patients who underwent surgery for CSM were reviewed. Median age was 62 (23-94) years and 59% were male. The median follow-up was 37 (17-88) months. The approach was anterior in 38 (42%) patients, posterior in 55 (58%); improvement was not significantly different when the two groups were compared. The number of levels decompressed increased with age (p value <0.0001). The group with a pre-operatively high signal on T1-weighted MRI images [n = 28 (30%)] was associated with less neurological recovery post-operatively compared to the patients with a normal T1 cord signal. None of the patients deteriorated neurologically post-operatively, while 66% improved by at least one NMG. CONCLUSION: Surgical decompressions for CSM stop the progress of symptoms at 12 months post-surgery and may result in a significant improvement of NMG in two-thirds of the patients. Changes in the T1-weighted MRI images predict worse outcomes following surgery.
Keywords: Magnetic Resonance Imaging; chirurgická dekomprese; magnetická rezonanční tomografie; Humans; MRI; lidé středního věku; Predictive Value of Tests; spondylóza; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Spinal Cord Diseases; Adult; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; nemoci míchy; Aged, 80 and over; Spondylosis; Young Adult; senioři nad 80 let; Cervical Vertebrae; Decompression; Cervical spondylotic myelopathy; mužské pohlaví; prospektivní studie; Decompression, Surgical; Outcome; krční obratle; Prospective Studies